The phenomenon of bioethics and aspects of medical ethics - Kotulskiy, Igor; Nikolchenko, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
This review article examines historical prerequisites for the appearance of bioethics as well as the sphere of its use and tasks in the modern medicine. It covers effective international legislative acts, which regulate procedures of biomedical researches (conventions, declarations, charters, etc.), approved at the level of such organizations as UNO, UNESCO, WHO, Council of Europe, UNEP. The authors cite legal regulations for conducting ethical expert examinations of scientific medical-biological researches in Ukraine, these regulations being aimed at protection of rights of patients and humane treatment of experimental animals.